Influence of pulse width on luminous efficiency for a two-degree field. (May 2017) - Fan, S; Zhang, X; Gu, X; Shen, H; Liu, M
A two-degree bipartite field was used to investigate the influence of pulse width on human luminous perception. The frequency of the pulsed light was 100 Hz and the duty ratio was set to 1, 2, 5, 10, 20, 30, 50 and 70%. The results show that pulsed light has a brightness enhancement effect and that the enhancement effect changes when the wavelength and duty ratio are different. The maximum enhancement effect appears at 430 nm and the minimum at 460 nm. Then, a theoretical spectral luminous function for pulsed light as a function of wavelength and duty ratio was calculated using cone fundamentals. The newly established luminous function can be used to calculate the real brightness perceived by human eyes when people are exposed to a space illuminated by pulse-width modulation dimming lamps.